Hygrothermal study of lightweight concrete hollow bricks: A new proposed experimental-numerical method - del Coz Diaz, J. J.; Alvarez-Rabanal, F. P.; Gençel, Osman; Garcia Nieto, P. J.; Alonso-Martinez, M.; Navarro-Manso, A.; Prendes-Gero, B.; Gençel, Osman (Elsevier Science Sa, 2014)
The aim of this paper is the development of a new hybrid methodology to study the moisture transport and heat transfer in masonry structures made up of light concrete hollow bricks (LWHBs) from the numerical and experimental points of view. In order to solve this coupled nonlinear hygrothermal analysis, an instrumented one square meter wall was subjected to eight different moisture stages in the laboratory using a special testing device during a total time of 1480 h. In order to simulate the different experimental stages, steady and transient states were implemented in the finite element models. Furthermore, the design of experiments methodology (DOE) and the goal design optimization (GDO) technique are used to calculate the best optimal parameters from the laboratory tests. Once the optimal parameters have been obtained, the finite element models for each stage are solved so that the moisture and temperature distributions were calculated. In this sense, a very good agreement between the numerical and experimental results is achieved. Finally, the most important conclusions of this study and advantages of this new methodology are exposed. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Finite Element Modeling; Light Concrete Hollow Bricks; Nonlinear Numerical Simulation; Coupled Hygrothermal Analysis; Hygrothermal Tests; Porous Media